2018
DOI: 10.1371/journal.pone.0193934
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar leak develops by a rich-get-richer process in ventilator-induced lung injury

Abstract: Acute respiratory distress syndrome (ARDS) is a life-threatening condition for which there are currently no medical therapies other than supportive care involving the application of mechanical ventilation. However, mechanical ventilation itself can worsen ARDS by damaging the alveolocapillary barrier in the lungs. This allows plasma-derived fluid and proteins to leak into the airspaces of the lung where they interfere with the functioning of pulmonary surfactant, which increases the stresses of mechanical vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 44 publications
8
38
1
Order By: Relevance
“…shown that increasing airway pressure in an acutely injured lung will cause a rapid progression of injury in a "rich-get-richer" power-law fashion, supporting the findings in the Guldner study (Hamlington et al, 2018). Combined, these studies suggest that high static stress and strain are associated with volutrauma in acutely injured lung tissue but not in normal lung tissue.…”
Section: Problems With Protecting the Baby Lungsupporting
confidence: 68%
See 2 more Smart Citations
“…shown that increasing airway pressure in an acutely injured lung will cause a rapid progression of injury in a "rich-get-richer" power-law fashion, supporting the findings in the Guldner study (Hamlington et al, 2018). Combined, these studies suggest that high static stress and strain are associated with volutrauma in acutely injured lung tissue but not in normal lung tissue.…”
Section: Problems With Protecting the Baby Lungsupporting
confidence: 68%
“…Both normal and acutely injured lung tissue are highly susceptible to high alveolar R/D-induced VILI when under high inflation pressure (Jain et al, 2017). These data support the rapid progression of lung injury in a power-law fashion when high static and dynamic strain are combined (Hamlington et al, 2018).…”
Section: Vili Mechanisms: Heterogeneous Alveolar Instability and Collsupporting
confidence: 54%
See 1 more Smart Citation
“…We postulate that as the lung opens, the increase in parenchymal tethering of airways [56] and alveolar interdependence [55] reduce lung pathology as a power-law function. Hamlington et al have shown that progressive lung injury advances in power-law fashion where alveolar R/D (atelectrauma) caused the initial holes in the epithelium and that high airway pressure (volutrauma) greatly expands these holes in a power-law or rich-get-richer fashion [60]. Lung protection also arguably follows a power-law function with reestablishment of parenchymal tethering, alveolar interdependence, and surfactant function all working together to accelerate recruitment and stabilization of adjacent tissue.…”
Section: New Concepts Of Ards Pathophysiologymentioning
confidence: 99%
“…Inflammatory response induced by CPB [16] could be exacerbated by accumulation of cytokines. Meanwhile mechanical ventilation itself could worsen ARDS by damaging the alveolocapillary barrier in the lungs [17]. The reduced compliance and a ventilation-perfusion mismatch hinted that the surfactant system was damaged [18,19].…”
Section: Discussionmentioning
confidence: 99%